O enfraquecimento das estruturas fortes e o retorno à religião : a proposta de Gianni Vattimo para o cristianismo contemporêneo - Vieira, Carlos Alberto Pinheiro (2011)
This paper reflects on the proposal for Gianni Vattimo to contemporary Christianity, whichis based on a weak ontology, in the process of deconstruction of the strongest structures of metaphysics in the West. Analysis, therefore, the possibility of a new interpretation of Christian faith in postmodern, themed by the philosophy of a post-metaphysical spirituality and post-religious. The research considers the various religious formatting contained within the Western culture, developing a critical evaluation of the propositions of a Christian religion without religion in contemporary society.